Investigating lung responses with functional hyperpolarized xenon-129 MRI in an ex vivo rat model of asthma - Lilburn, David M.L.; Tatler, Amanda L.; Six, Joseph S.; Lesbats, Clémentine; Habgood, Antony; Porte, Joanne; Hughes-Riley, Theodore; Shaw, Dominick E.; Jenkins, Gisli; Meersmann, Thomas (Wiley, 2015)
Purpose: Asthma is a disease of increasing worldwide importance that calls for new investigative methods. Ex vivo lung tissue is being increasingly used to study functional respiratory parameters independent of confounding systemic considerations but also to reduce animal numbers and associated research costs. In this work a straightforward laboratory method is advanced to probe dynamic changes in gas inhalation patterns by utilizing an ex vivo small animal ovalbumin (OVA) model of human asthma. Methods: Hyperpolarized (hp) 129Xe was actively inhaled by the excised lungs exposed to a constant pressure differential that mimicked negative pleural cavity pressure. The method enabled hp 129Xe MRI of airway responsiveness to intravenous methacholine (MCh) and airway challenge reversal through salbutamol. Results: Significant differences were demonstrated between control and OVA challenged animals on global lung hp 129Xe gas inhalation with p < 0.05 at MCh dosages above 460 μg. Spatial mapping of the regional hp gas distribution revealed an approximately 3 fold increase in heterogeneity for the asthma model organs. Conclusion: The experimental results from this proof of concept work suggest that the ex vivo hp noble gas imaging arrangement and the applied image analysis methodology may be useful as an adjunct to current diagnostic techniques.